1983
DOI: 10.1126/science.6828889
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Cholinergic Receptor Binding Sites in the Brain: Regulation in Vivo

Abstract: Tritiated acetylcholine was used to measure binding sites with characteristics of nicotinic cholinergic receptors in rat brain. Regulation of the binding sites in vivo was examined by administering two drugs that stimulate nicotinic receptors directly or indirectly. After 10 days of exposure to the cholinesterase inhibitor diisopropyl fluorophosphate, binding of tritiated acetylcholine in the cerebral cortex was decreased. However, after repeated administration of nicotine for 10 days, binding of tritiated ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
270
4
3

Year Published

1986
1986
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(291 citation statements)
references
References 13 publications
14
270
4
3
Order By: Relevance
“…We found that knock-down of c-Fos inhibited the nicotine-induced excitatory status of cells but not the expression of TH ( Figure 8A and A1), indicating that the effect of c-Fos on the excitatory status of cells and neuron-specific adaptation induced by nicotine was not mediated by the regulation of TH expression. The binding sites of the 3 H nicotine in the central nervous system as well as the number of cells that can react to nicotine were increased after prolonged nicotine exposure [37,38]. Our present study indicates that L-theanine can inhibit the rewarding effects in the mouse CPP model and reduce the excitatory status of cells induced by nicotine.…”
Section: Discussionsupporting
confidence: 51%
“…We found that knock-down of c-Fos inhibited the nicotine-induced excitatory status of cells but not the expression of TH ( Figure 8A and A1), indicating that the effect of c-Fos on the excitatory status of cells and neuron-specific adaptation induced by nicotine was not mediated by the regulation of TH expression. The binding sites of the 3 H nicotine in the central nervous system as well as the number of cells that can react to nicotine were increased after prolonged nicotine exposure [37,38]. Our present study indicates that L-theanine can inhibit the rewarding effects in the mouse CPP model and reduce the excitatory status of cells induced by nicotine.…”
Section: Discussionsupporting
confidence: 51%
“…(c) Adaptations in nAChR function Chronic nicotine administration leads to an interesting paradoxical change in the function of nAChRs, which consists of receptor desensitization leading to receptor upregulation (Marks et al 1983;Schwartz & Kellar 1983;Changeux et al 1984;Wonnacott 1990;Flores et al 1997;Perry et al 1999;. Complex theoretical speculations have been put forth about the role of nAChR desensitization and upregulation in the subjective effects of acute nicotine and in the development and maintenance of nicotine dependence ( Marks et al 1992;Dani & Heinemann 1996;Buisson & Bertrand 2002;Quick & Lester 2002).…”
Section: Neurosubstrates Of Nicotine Reward Dependence and Withdrawalmentioning
confidence: 99%
“…However, in this work, we will be focusing on the a4b2 heteromeric receptor in terms of its translational importance. In contrast to other subtypes, the a4b2 nAChR subtype has been shown to readily up-regulate following chronic exposure to nicotine, as evidenced by findings in cell culture (Xiao and Kellar 2004), rodents (Schwartz and Kellar 1983;Marks et al 1985), monkeys (Picciotto et al 2008), and humans (Mukhin et al 2008). The up-regulation of receptors in the face of increased agonist is a characteristic unique to nicotine, and its full importance is not understood.…”
Section: Neurochemisty Of Nicotinementioning
confidence: 99%